Application of Electrical Resistivity Tomography (ERT) survey for investigation of the landslide: a case study from Taprang landslide, Kaski district, west-central Nepal (Journal of Nepal Geological Society, 2020)
The depth of the slip surface and thickness of the overburden deposit play a major role in assessing the slope stability of a landslide. Electrical Resistivity Tomography (ERT) survey was carried out in the Taprang Landslide, Kaski district, west- central Nepal to determine subsurface lithological conditions, depth and geometry of the slip surface. Wenner and dipole- dipole arrays were mainly applied in this ERT survey. The electrical resistivity survey revealed that there is a wide range of resistivity value which shows different kinds of layers in the subsurface, and the boundaries between these layers played a significant role to identify the slip surface. The data show mainly three layers from surface to bottom. An upper layer represents the dry to saturated colluvium and sandy gravelly soil (500 to 8000 Ωm), the middle layer is highly –saturated soil with low resistivity value (100–700 Ωm) and unweathered fresh bedrock of schist and quartzite with high resistivity value (1000 to 8000 Ωm) at the bottom layer. The slip surface is considered as depth 25 m at the crown, 10–20 m at the main body part, and below 50 m at the toe and curved in geometry which indicates the rotational type of landslide. Investigation of the slip surface in a landslide using the ERT survey aids to know the slope stability.